AKTIVITAS ANTIBAKTERI EKSTRAK DAUN BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP BAKTERI PATOGEN PANGAN - Soedirga, Lucia Crysanthy (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2019)
Antibacterial activity of Averrhoa bilimbi leaves extracts on pathogenic bacteria was observed in this study by using well diffusion method. The leaves were extracted using maceration method with three different solvents, i.e. ethanol (polar), ethyl acetate (semi polar), and hexane (non polar). Moreover, different concentrations (5,10,15,20, and 25%) of bilimbi leaves extract were also observed in this study in order to determine which solvent and concentration gave the highest antibacterial activity against B.cereus, S.aureus, Pseudomonas sp., and Enterobacter sp. Further objectives of this research were to determine the MIC and MBC for each bacteria from the selected extract. The result showed that ethanol extract gave the highest antibacterial activity with inhibition diameter ranging from 2.55 mm for Enterobacter sp. to 12.36 mm for B.cereus. Moreover, MIC and MBC for Gram negative higher than the MIC and MBC for Gram positive.